(untitled) (University Journal of Zoology, Rajshahi University, 2008)
Eggs of the lesser mealworm, Alphitobius diaperinus (Panzer) were exposed to UV-rays of 254nm wavelength for different durations viz. 1, 2, 4 and 8 minutes. After seven days of hatching, larvae of each exposure were reared separately on triflumuron (1 x 10-3 mg/kg) treated food and observed the population of various developmental stages e.g., egg, larval, pupal and adult at storage periods of 3-, 6- and 9-months. UVrays and triflumuron treatments deleteriously reduced the populations of all the developmental stages of A. diaperinus. Egg and pupal populations of the beetle were adversely influenced by the storage periods also. Complete reduction of A. diaperinus populations was achieved from 6-9 months storage periods, when eggs were exposed to UV-rays for 8 minutes. Key words: Mealworm, UV-rays, IGR, progeny production Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 45-48